The nature of language learners’ beliefs: A half-told story - Zhong, Qunyan (Maggie) (International Journal of English Studies, 2015)
Substantial amount of research regarding L2 learners’ beliefs has been conducted in recent years. However, not enough attention has been paid to investigating the nature of learners’ beliefs; hence our understanding of the construct is contradictory in the sense that early research studies report stability in beliefs, while more recent studies provide evidence of change in learners’ beliefs. This paper reports on a case study aiming at contributing to a deeper understanding of the nature of language learners’ beliefs. Data were gathered longitudinally over an 18-week period using a number of tools. The findings reveal the complexity of learners’ beliefs. The beliefs that the learners held were not always in harmony and some of them can be self contradictory. Furthermore, while some beliefs may evolve and change over time and across situation, others may remain relatively stable, suggesting the complex and dual nature of learners’ beliefs. Drawing on these findings, the paper concludes that learner beliefs can best be perceived as an inter-related construct that has dual features and sometimes can be paradoxical.